Advances in 2D Molybdenum Disulfide Transistors for Flexible and Wearable Electronics - Kyoungwon Kwak; Hyewon Yoon; Seongin Hong; Byung Ha Kang (Micromachines)
As the trajectory of developing advanced electronics is shifting towards wearable electronics, various methods for implementing flexible and bendable devices capable of conforming to curvilinear surfaces have been widely investigated. In particular, achieving high-performance and stable flexible transistors remains a significant technical challenge, as transistors are fundamental components of electronics, playing a key role in overall performance. Among the wide range of candidates for flexible transistors, two-dimensional (2D) molybdenum disulfide (MoS2)-based transistors have emerged as potential solutions to address these challenges. Unlike other 2D materials, the 2D MoS2 offers numerous advantages, such as high carrier mobility, a tunable bandgap, superior mechanical strength, and exceptional chemical stability. This review emphasizes the novel techniques of the fabrication process, structure, and material to achieve flexible MoS2 transistor-based applications. Furthermore, the distinctive feature of this review is its focus on studies published in high-impact journals over the past decade, emphasizing their methods for developing MoS2 transistors into various applications. Finally, the review addresses technical challenges and provides an outlook for flexible and wearable MoS2 transistors.